Maturation and anthropometric correlates of aerobic capacity in top elite young female volleyball players: PWC170 vs. step test - Nikolaidis, P. T.; Kostoulas, I.; Tasiopoulos, I.; Padulo, J.; Torres-Luque, G.; Fernández-Garcia, A. I.; Alfonso, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: From a physiological point of view, performance in volleyball relies mostly on anaerobic power and anthropometry (1-6). Nonetheless a minimum of aerobic capacity is necessary for volleyball players to cope with the demands of training and certain game situations (e.g. long-lasting rallies). Whether two inexpensive tests of aerobic capacity, the physical working capacity at heart rate 170 bpm (PWC170) and YMCA step test, can be used interchangeably has not been examined yet. The aim of the present study was to examine the relationship between the YMCA step test and PWC170 in top elite young female volleyball players. Methods: Forty-three selected female volleyball players (age 13.0 (0.6) yrs, height 171 (6) cm, weight 61.6 (6.6) kg)) performed a series of anthropometric and aerobic capacity tests (PWC170 and YMCA step test). Results: HR in the end of YMCA test correlated with PWC170 indices (0.780.087). Conclusions: PWC170 and YMCA test showed very large correlations and their use in young volleyball players is further recommended. The lack of relationship of aerobic capacity with anthropometric and age parameters should be considered in training planning by coaches and fitness trainers.